(untitled) (Scientific Journal for Faculty of Science-Sirte University, 2024)
The histocompatibility complex (MHC) system is important in immunity to intracellular pathogens such as Leishmania parasites. MHC-I expression is regulated after the infection, and it is a pivotal mechanism used by intracellular pathogens to evade the immune response. Very little is known about this mechanism of Leishmania infection. In this study, the infection with different growth phases of Leishmania mexicana effect on MHC-I expression was evaluated in human cell line U937 and MonoMac-6 by flow cytometry. The results clearly show a wide range of MHC-I downregulation due to the infection of human cells with different phases of L. mexicana. MHC-I expression was significantly (P<0.05) downregulated when U937 and MonoMac-6 cells were infected with mid log stage at a ratio of 1:10 (cell:parasite), compared to infection with late and stationary phases. The results illustrated that MHC-I expression was down regulated from 88% in control cells to 79.00%, 45.08%, and 1.74% at infection ratios of 1:10, 1:20, and 1:30, respectively. Therefore, the degree of MHC-I downregulation was parasite dosage dependent. The normal MHC-I appearance in parasite infected cells was partially restored after adding fungizone, an anti Leishmania agent. In conclusion, the previously documented fluctuations in MHC-I expression responses to Leishmania infection may relate to differences in the parasite’s development stages and infection dose.